1996
DOI: 10.1016/0376-7388(95)00128-x
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of alkanes through ceramic thin zeolite MFI membranes

Abstract: Polycrystalline randomly oriented defect free zeolite layers on porous o~-A1203 supports are prepared with a thickness of less than 5/zm by in situ crystallisation of silicalite-1. The flux of alkanes is a function of the sorption and intracrystalline diffusion. In mixtures of strongly and weakly adsorbing gases and at high loadings of the strongly adsorbing molecule in the zeolite pore, the flux of the weakly adsorbing molecule is suppressed by the sorption and the mobility of the strongly adsorbing molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(143 citation statements)
references
References 8 publications
8
133
2
Order By: Relevance
“…The MFI membrane permeation selectivity is found experimentally to be strongly in favor of the linear isomer. 67,70 A further point to stress is that nC4/iC4 separations using MFI in both fixed bed adsorbers and membrane devices benefit from the synergy between adsorption and diffusion; both of these act in favor of the linear isomer. This has been established in the MAS PFG NMR experiments of Fernandez et al 71 and the transient uptake data of Chmelik et al 72 Tijsebaert et al 73 have demonstrated the potential of RUB-41, which has the RRO zeolite structural topology, for separation of cis-2-butene and trans-2-butene from 1-butene; this separation is of industrial importance because 1-butene is needed in the production of e.g.…”
Section: Separation Of C4 Hydrocarbonsmentioning
confidence: 99%
“…The MFI membrane permeation selectivity is found experimentally to be strongly in favor of the linear isomer. 67,70 A further point to stress is that nC4/iC4 separations using MFI in both fixed bed adsorbers and membrane devices benefit from the synergy between adsorption and diffusion; both of these act in favor of the linear isomer. This has been established in the MAS PFG NMR experiments of Fernandez et al 71 and the transient uptake data of Chmelik et al 72 Tijsebaert et al 73 have demonstrated the potential of RUB-41, which has the RRO zeolite structural topology, for separation of cis-2-butene and trans-2-butene from 1-butene; this separation is of industrial importance because 1-butene is needed in the production of e.g.…”
Section: Separation Of C4 Hydrocarbonsmentioning
confidence: 99%
“…15 Moreover, experiments show that the linear/branched separation selectivity increases with increasing nonframework cation density inside MFI-type channels. 13,[26][27][28] To the best of our knowledge, only a few groups have performed molecular simulations in MFI-type structures with alkali metal nonframework cations. [29][30][31][32][33] This may be because the commercial interest for alkali-exchanged MFI zeolites has been less than that for LTA and FAU (structures used to separate oxygen from air in pressure swing adsorption 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…It will not only cut the equipment and operation cost off, but also be operated continuously if the zeolites can be configured into a membrane form. Since 1990s, much effort has been paid in the synthesis of zeolite membrane [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Till now, different types of zeolite membranes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…butane isomers. Although high separation factors have been obtained for these mixtures, the MFI zeolite membrane has not shown good separation performance for permanent gases or permanent gas/organic gas because of the large pore size and the hydrophobic nature of the zeolite [12][13][14][15]. Therefore, the investigation of the zeolite membranes with small pore size has attracted much attention [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%